Biomarker Validation: Context and Complexities. Issue 3 (2019) - McShane, Lisa M.
Abstract : Validation of a biomarker-based medical product development tool or clinical test is an evidentiary process that must be tailored to the proposed use. Appropriate data and analyses are needed to demonstrate that the biomarker meets analytical and clinical performance criteria consistent with favorable benefit: risk balance.